Matrimonial Regimes - MOLDOVAN, Iosif Florin (Journal of Legal Studies, 2015)
The matrimonial regime represents the entirety of the legal provisions concerning the property relations between spouses during marriage, as well as the legal documents they conclude with other people, governing a (measurable) patrimonial asset. In addition to the legal community regime, with the adoption of the new Civil Code two new matrimonial regimes were introduced, namely the regime of property separation and the regime of the conventional community. Where the two spouses opt for one of the other two regimes, instead of the legal community regime, it is necessary that they should sign a marital agreement.